SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN SISWA DENGAN MENGGUNAKAN METODE ENTROPI - Andri Sukmaindrayana (JUTEKIN (Jurnal Teknik Informatika), 2017)
An education institutions often require a system of decision-making in determining admissions. So it takes a decision support system that can determine which students may be accepted by considering the abilities, talents and interests of students, which can help decision-makers nature where the decision results can be used as material to assist teachers in making decisions.             In line with the development of information technology, so does the ability of the computer to help solve problems in shared areas, including computer-based decision support systems (Computer Based Decision Support System). The system is designed to improve the effectiveness of decision makers in solving problems faced by both the problem of semi-structured or unstructured.Kata Kunci : DSS, Siswa, Entropi